Revealing Tyndaris: a Technological Approach to Archaeological Conservation and Study - Redazione MediaGEO; Andrea Di Santo; Michele Fasolo (Archeomatica)
The archaeological site of Tyndaris (currently Tindari, municipality of Patti, province of Messina, Italy) served as the backdrop for an important technological and cultural initiative organized by mediaGeo on May 30, 2024: the “Technology for All on the Road 2024”. The event brought together university professors, experts in geomatics, archaeology, and engineering, as well as industry professionals engaged in applying advanced surveying methodologies. The main objective was to create precise and detailed digital documentation of a site useful for conservation, study, and tourism enhancement. During the event, a series of stateof- the-art surveying technologies were employed to map and meticulously document the topography and monuments of the ancient Greek, and later Roman, city in Sicily— an area for which a complete survey is still lacking.